2014
DOI: 10.4049/jimmunol.1400736
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Vitamin D Regulates Lipid Metabolism in Mycobacterium tuberculosis Infection

Abstract: Vitamin D has long been linked to resistance to tuberculosis, an infectious respiratory disease that is increasingly hard to treat due to multidrug resistance. Previous work established that vitamin D induces macrophage antimicrobial functions against Mycobacterium tuberculosis. Here we report a novel, metabolic role for vitamin D in tuberculosis identified through integrated transcriptome and mechanistic studies. Transcriptome analysis revealed an association between vitamin D receptor (VDR) and lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 18 publications
2
81
0
1
Order By: Relevance
“…Lysolipids are phospholipids that have had one or more acyl group removed (by hydrolysis). Vitamin D has multiple effects on lipid metabolism through its actions on nuclear hormone receptors, such as the vitamin D receptor and PPARγ (30), including changing the phospholipid content of cells (31). Thus, our results are consistent with the effects of vitamin D on lipid metabolism mediated through these receptors.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 80%
“…Lysolipids are phospholipids that have had one or more acyl group removed (by hydrolysis). Vitamin D has multiple effects on lipid metabolism through its actions on nuclear hormone receptors, such as the vitamin D receptor and PPARγ (30), including changing the phospholipid content of cells (31). Thus, our results are consistent with the effects of vitamin D on lipid metabolism mediated through these receptors.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 80%
“…42 Several in vitro studies have recently demonstrated that VDR and PPAR-g signaling pathways interact and there is evidence of "crosstalk," although the detailed mechanisms have not been elucidated. 42,44,45 In one study, PPAR-g was found to monopolize RXR-a available for VDR binding and there was an inverse relationship between VDR and PPARg basal expression in these cell lines. 44 The promotor region of certain human PPAR genes contains a potent VDRE (vitamin D response element).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that M. tuberculosis infected macrophages differentiate into lipid rich foam cells by accumulating lipid droplets that are required for its intracellular growth [48,49] . Another recent study reported that vitamin D 3 treatment inhibited the accumulation of lipid droplets in infected macrophages by downregulating the expression of proadipogenic peroxisome proliferator-activated receptor-γ (PPAR-γ) and control the growth of intracellular M. tuberculosis [50] .…”
Section: Invasive Mechanisms Of M Tuberculosis In Macrophagementioning
confidence: 99%